Community-Based Healthy Lifestyle Intervention Program (Co-HELP) Modification Meningkatkan Kualitas Hidup Pasien DM - Tubalawony, Syulce Luselya; Prabawati, Fransiska Dewi (UIMA Press, 2020)
Background: The modern era that occurs couses lifestyle changes such as hing consumption patterns of fast food and lock of physical activity couses an increase in cronic diseases, one pf them Diabetes Mellitus (DM). The purpose of this study was to analyze the effectiveness of community-based healthy lifestyle intervention program (Co-HELP) Modification in DM patients at the Waai Health Center, Ambon. Methods: Quasy experiments were utilize. There were 76 respondents which chosen using purposive sampling techniques and divided into 2 groups where 51 respondents into intervention group and 25 respondents as control group. Quality of life was measured by DQOL questionnaire. Analysis of research results with the Wilcoxon and Mann-Whitney test Results: It was revealed that majority of respondents on the elderly category, women (77.6%), suffer from DM >5 years (67.1%), light work (82.9%). After 6 weeks of Co-HELP Modification, statistical test declared that there were significant differences in quality of life (DQOL) (p = 0,000), fasting blood sugar (FBS) levels (p=0,000) pre-post intervention, however there were no significant difference for systole and diastole blood pressure. The logistical regression test revealed that Co-HELP Modification intervention, age, gender, long suffered from DM and occupation were significant impact to quality of life simultaneously (p=1,000),blood glucose (p=0,975), SBP (p=1,000) and DBP (p=0.315). Conclusion: It is recommended to implement Co-HELP Modification as a preventive aspect to prevent complication so that quality of life improves